THE DEVELOPMENT OF AN AUGMENTED REALITY TECHNOLOGY APPLICATION USING ADDIE MODEL ON PACKAGING - Nafisah Mat Nasir; Noor Azly Mohammed Ali (International Journal of Accounting, Finance and Business, 2022)
This research discusses Augmented Reality (AR) technology applications that we useto incorporate virtual information into the physical world. Due to the recent development oftechnology, augmented reality is commonly found to be one of the interactive experiences of areal-world environment refers to the objects being augmented. Augmented Reality (AR) hasemerged as a new trend technology not only in gaming applications but also in productpackaging. Indeed, augmented reality has numerous applications in the packaging industrynowadays. This technology can provide numerous benefits, including improving productpackaging, increasing brand loyalty, attracting new customers, and differentiating productpackaging from competitors. However, it is less focused on integrating the development of ARspecific on the packaging due to the lack of academic studies in the field of AR packaging.Other than that, there is no standard design process for visual interfaces with augmented realityeven though there are many success stories about the use of AR by brands that have beenhighlighted in technology reviews from other countries but are very reluctant in Malaysia. Thisstudy will discuss the role of augmented reality in packaging and determine the process ofaugmented reality development on the packaging. At the end of this research, we suggest aresearch framework to initiate the development of Augmented Reality technology applicationsusing the ADDIE model on the packaging. A qualitative method has been used to collect data,where a survey through a closed-ended questionnaire instruments interviews with three expertsespecially in creative industry. Interview results, showed that the packaging product suitableto implement with AR technology as a prototype was food and beverages industry example BeeHoney product packaging. For future studies, it is expected that will assist researchers, creativeindustry practitioners, and packaging product marketers that will bring better improvementand implement augmented reality on the packaging by using this framework.